Wealth Inequality and Tuberculosis Elimination in Europe - Suk, Jonathan E. (Centers for Disease Control and Prevention, 2009)
In Europe, wealth inequality is directly related to tuberculosis (TB) notification (R(2) = 0.69), while in countries with lower TB rates, higher proportions of TB cases occur in foreign-born persons. Particularly during times of financial upheaval, efforts to eliminate TB must address social inequality.